No me agarran viva. Mental Structures and the Liberation Process (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
From the point of view of liberation philosophy expressed principally by Paolo Freire and Gustavo Gutierrez, this article examines the structure of a testimonial novel that deals with the civil war in El Salvador in the 1980’s. While the novelist means to showcase the Marxist forces as a model of solidarity with the common people, a close reading of the text reveals a pattern of elitist and paternalistic attitudes that undermine her purpose.